Analysis of Students Chinese-Indonesian Translation of Cultural Terms Translation - Arini Junaeny; Nirdayanti Nirdayanti (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
This research aims to analyse students’ translation work of Chinese cultural terms. Cultural translation has difficulties with specific cultural terms whether in words or idioms. This research is using descriptive qualitative method. Data was collected from the work of students in translating Hong Lou Meng and Hua She Tian Zu. With the theories as a reference, the author analyses the error and quality of students' work. According to Newmark’s V diagram translation method, the students’ translation from Chinese language to Indonesian language mostly used word-for-word translation and Literal translation. In student translation works, there are also several mistakes found, such as the vocabulary, word order, or structure that influence the quality of translation. Chinese translate into Indonesian language as TL is too stiff and lack of natural language. From the weakness of student’s translation ability, here are suggestions to increase their translation ability: 1) More experience to use Chinese language in daily activities can help to increase the sense of language.Language cannot be separated from culture; 2) Students have to learn and experienced more about Chinese culture; 3) Students can learn and practice translation from many sources.